Meeting an Early Medieval Community: A Preliminary Analysis of the Human Skeletal Remains from the Jucu Cemetery (Cluj-Napoca, Romania) - Diana, A.; Meșter, M. (Materiale și Cercetări Arheologice, 2013)
The cemetery of Jucu – “Tetarom III“-was excavated in 2007, part of a commercial archaeological project triggered by the construction of the Nokia industrial park. The investigated area proved to be extremely rich, the traces of human habitation covering a rather extensive time period, from the Early Prehistory (Neolithic) to the XVIII century AD. This paper presents the preliminary results of the osteological analyses carried out on 60 individual skeletons. The study suggested higher rates of mortality among juveniles, slight differences in the distribution of pathological lesions between females and males, and an average stature similar to that of other North-Central Early Medieval populations in Europe. The cemetery of Jucu was used during a time period characterised by intense population movements. Given the limited number of written documents pertaining to the early Middle Ages in Transylvania, archaeological and osteological evidence is vital to our understanding of this region’s history. The present research constitutes only a pilot study but has provided extremely valuable information about the post-Roman community whose members were enterred at Jucu